2020
DOI: 10.2147/tcrm.s247437
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pretreatment with Nalbuphine Prevents Sufentanil-Induced Cough During the Anesthesia Induction: A Randomized Controlled Trial</p>

Abstract: Background: Sufentanil-induced cough is frequent during the induction of anesthesia. The aim of this research was to assess the influence of pretreatment with nalbuphine on sufentanil-induced cough. Patients and Methods: A total of 210 American Society of Anesthesiologists (ASA) I-II patients who are 18-70 years old and scheduled for elective surgery were randomly divided into two groups. Group N was pretreated with 0.3 mg/kg nalbuphine at 150 s before induction with sufentanil, and Group C received the same v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Explosive cough may increase intraabdominal pressure and increase the risk of regurgitation and aspiration [5]. Clinical interventions have been reported to reduce SIC [1][2][3][6][7][8][9][10][11][12][13], including pretreatment with drugs (butorphanol, dezocine, remifentanil and dexmedetomidine), changing the administration route or diluting the concentration of sufentanil. However, the interventions were restricted in clinical use due to several side effects, such as long onset time, bradycardia, and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Explosive cough may increase intraabdominal pressure and increase the risk of regurgitation and aspiration [5]. Clinical interventions have been reported to reduce SIC [1][2][3][6][7][8][9][10][11][12][13], including pretreatment with drugs (butorphanol, dezocine, remifentanil and dexmedetomidine), changing the administration route or diluting the concentration of sufentanil. However, the interventions were restricted in clinical use due to several side effects, such as long onset time, bradycardia, and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Explosive coughs may increase intra-abdominal pressure, increasing the risk of regurgitation and aspiration [5]. Clinical interventions, such as pretreatment with drugs (butorphanol, dezocine, remifentanil, and dexmedetomidine), changing the administration route or diluting the concentration of sufentanil, have been reported to reduce SIC [1][2][3][6][7][8][9][10][11][12][13]. However, the interventions could not be widely implemented in clinical practice due to several side effects such as long onset time, bradycardia, and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…Due to different doses, routes of use, and population, opioids may have a series of adverse effects, such as nausea, vomiting, cough, addiction, urinary retention, and even respiratory depression [2]. Studies have shown that the incidence of cough caused by fentanyl, remifentanil, and sufentanil was 32% [3], 27.6% [4], and 28.5% [5], respectively. Coughing caused by the application of sufentanil is called sufentanil-induced cough (SIC) [6].…”
Section: Introductionmentioning
confidence: 99%
“…SIC is generally transient, self-limiting, and benign in general anesthesia [8,9]. According to the number of coughs recorded, the severity of cough was divided into mild (1)(2), moderate (3)(4)(5) and severe (> 5) [6]. Studies have shown that SIC occurs mostly within 1 min of intravenous injection of opioids [6,10,11].…”
Section: Introductionmentioning
confidence: 99%